Exploring pre-service teachers' reflective practice through an analysis of six-stage framework in reflective journals. Issue 5 (3rd September 2022) - Yee, Bee Choo; Abdullah, Tina; Mohd Nawi, Abdullah
ABSTRACT: Reflective journal is used by the pre-service teachers (PSTs) to reflect on their learning and teaching experiences in the classroom but they lack writing it in a more critical way. This study aims to explore the common stages of reflective practice among the PSTs using a six-stage framework. The methodology utilised a case study involving a purposive sampling of a group of 20 participants in an institute of teacher education in Malaysia. The instruments were observations, reflective journals and interviews. The journals were analysed using content analysis by following the framework of reflective practice. The results showed that the PSTs reflected mostly at 'Describing' (36.04%), followed by 'Analysing' (26.00%), 'Associating' (21.15%), 'Feeling' (12.12%), 'Assessing' (2.78%), and 'Developing' (1.92%). The findings indicated that the PSTs reflected mostly at the lowest stage of 'Describing' compared to the highest stage of 'Developing'. It is also interesting to note that the PSTs reflected more deeply after they were able to project their feelings and receive peer feedback. The six-stage framework used in this study not only provides the PSTs a guideline to reflect deeply, but also allows them to develop their future roles as teachers. The implication is for the policy makers and educators to include the proposed framework in the course syllabus and it is recommended for the PSTs to use it as a guideline in developing their reflective practice.